Policing wildlife trafficking in northeastern Mexico: the case of Tamaulipas in 2023-2024 - Carpio-Domínguez, José Luis; Cervantes-Niño, José Juan; Castro-Salazar, Jesús Ignacio; Mendezcarlo-Silva, Violeta (Frontiers in Conservation Science, 2025)
Illegal wildlife trade is an environmental, economic, and social problem that threatens global public health and the security of countries. It is one of the main drivers of biodiversity loss on a global scale. Mexico is a source and transit nation for trafficked wildlife, so the timely detection by Mexico’s governmental institutions is of fundamental importance for combating wildlife trafficking. The present study aims to analyze the factors that facilitate or constrain the police actions taken as first responders to wildlife trafficking in the state of Tamaulipas during the period 2023-2024. Through interviews with police officers, we determined that the prioritization of crimes related to public security has limited police attention to other forms of crime, such as wildlife trafficking. as the outcome is that wildlife trafficking is a largely uninvestigated, unquantified, and unaddressed crime. Further, most police officers are unaware that environmental crimes fall under their jurisdiction, which limits law enforcement and environmental justice in the state.